'To prove I'm not incapable, I overcompensate': Disability, ideal workers, the academy. (December 2022) - Humphrys, Elizabeth; Rodgers, Jess; Asquith, Nicole L; Yaghi, Sally Anne; Foulstone, Ashleigh; Thorneycroft, Ryan; Cook, Peta S
The experiences of academics with disability have received modest but growing attention internationally, but virtually none in the Australian context. This article outlines research findings from a study examining their experiences at a large Australian university. The article uses a materialist framework to demonstrate how capitalist social relations shape and demarcate an 'ideal university worker', how disabled workers find it difficult to meet this norm, and the limited assistance to do so provided by managers and labour relations policy frameworks. The research findings point to a profound policy gap between employer and government disability policy inclusion frameworks and the workplace experience of academics. This breach requires further investigation and, potentially, the development of alternate strategies for workplace management of disabilities if there are to be inroads towards equity. JEL codes: Z13